Hippo Pathway Counter-Regulates Innate Immunity in Hepatitis B Virus Infection - Luo, Xufeng; Zhang, Rui; Lu, Mengji; Liu, Shi; Baba, Hideo A.; Gerken, Guido; Wedemeyer, Heiner; Broering, Ruth (Frontiers in Immunology, 2021)
Whether hepatitis B virus (HBV) activates or represses innate immunity continues to be debated. Toll-like receptor (TLR) 2 has been identified to recognize HBV particles in human hepatocytes. The Hippo pathway, known for growth control, is suggested to play a vital role in immune regulation. Here, molecular interactions between HBV-triggered TLR signaling and the Hippo pathway were comprehensively investigated. Reanalysis of GSE69590 data, in which human hepatocytes have been treated with cell culture-derived HBV particles, identified changes in Hippo and NF-κB signaling. Immunocytochemical staining and western blotting revealed time-dependent nuclear translocation of YAP and NF-κB in HBV-exposed primary human and murine hepatocytes (PMH). Analysis of PMH isolated from MyD88- or IRAK4-deficient mice and the inhibition of TLR2 and MST1/2 in vitro confirmed the relation between TLR2 and Hippo signaling in HBV-induced immunity. Loss and gain of function experiments implied that Hippo-downstream effector YAP directly regulated IκBα expression. Functional investigations confirmed the regulation of Nfkbia promoter activity by the YAP/TEAD4 transcription factor complex. Administration of TLR ligands to mice highlighted the relevance of the TLR2-MyD88-IRAK4-Hippo axis in hepatic immunity. Interestingly, reanalysis of gene expression pattern in liver biopsies of patients chronically infected with HBV (GSE83148, GSE65359) indicated an activation of TLR2 and however, an MST1-dominated Hippo control in the immune clearance phase of patients with chronic HBV infection. We demonstrated that MyD88-dependent TLR signaling activates NF-κB and Hippo signaling, with YAP prompting the IκBα-mediated negative feedback, alongside NF-κB. Imbalance between immune induction and Hippo activation may have implications for the safety of novel HBV cure strategies interfering with pathogen recognition receptors.